Metapetrocosmea navicularis, a new species of Gesneriaceae in Vietnam - Qi-Yang Li; Ke Tan; Truong Van Do; Zi-Bing Xin; Xin-Xiang Bai; Song-Tao He; Fang Wen (PhytoKeys)
Based on morphological comparisons, literature reviews, and molecular systematic studies, a new species from South Vietnam, Metapetrocosmea navicularis F.Wen, T.V.Do, Z.B.Xin & K.Tan, has been confirmed. Morphologically, this new species resembles Metapetrocosmea tamiana (B.L.Burtt) Yin Z.Wang & P.W.Li in leaf peltate, bilabiate corollas, arcuate filaments, and slightly curved capsule, while it is distinguished from M. tamiana in having leaf blade ovate to ovate-elliptic, boat-shaped bracts 6–9 mm long, the ratio of corolla lobes length to corolla tube length consistently 1 : 3, corolla tube gradually narrowed from mouth to base, subcylindrical-infundibulate, 10–20-flowered or more, filaments pubescent near the top. Molecular phylogenetic analyses using the combined dataset of trnL-F and ITS sequences show that the new species is also most closely related to M. tamiana. The conservation status of this new species is assessed as Least Concern (LC).